1994
DOI: 10.1111/j.1752-7325.1994.tb01211.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Milk as a Saliva Substitute

Abstract: Xerostomia, a clinical manifestation of salivary gland dysfunction, affects many people. These individuals frequently sip liquids to alleviate the discomforts associated with hyposalivation. Milk appears to have many of the chemical and physical properties of a good saliva substitute. Besides the obvious benefit of providing moisture and lubrication for the dehydrated mucosa, milk buffers oral acids, reduces enamel solubility, and contributes to enamel remineralization. These anticariogenic factors are general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Nutrient intake in Sjögren's syndrome JM Cermak et al xerostomia (Herod, 1994). In support of this hypothesis, analysis of the milk consumption in our study subjects shows that women with 1 SS drink significantly more milk per week than 2 SS=SLE, 2 SS=RA or control individuals (data not shown).…”
Section: Discussionsupporting
confidence: 74%
“…Nutrient intake in Sjögren's syndrome JM Cermak et al xerostomia (Herod, 1994). In support of this hypothesis, analysis of the milk consumption in our study subjects shows that women with 1 SS drink significantly more milk per week than 2 SS=SLE, 2 SS=RA or control individuals (data not shown).…”
Section: Discussionsupporting
confidence: 74%
“…Similar effects have been observed after the immersion of demineralized enamel samples in cow's milk [8]. Milk also contains calcium and phosphate in sufficiently high concentrations and has been suggested as a saliva substitute [13].…”
Section: Discussionsupporting
confidence: 64%
“…Ever since Lady May Mellanby (1929,1930) proposed milk as an important nutritional factor affecting pre-eruptive tooth mineralization and post-eruptive caries resistance, the relationship between milk and caries has been examined from various angles [for a review, see Reynolds and Storey (1979) and Herod (1991Herod ( ,1994]. Although Mellanby's theory was not tenable, numerous animal studies have demonstrated that milk and milk products (primarily cheese) have a protective effect against the development of dental caries (Bevetta and McClure, 1957;Shaw et al, 1959;Dreizen et al, 1961; Reynolds and Del Rio, 1984;Harper et al, 1986;Reynolds and Black, 1987;Bowen and Pearson, 1993;Mundorff-Shrestha et al, 1993).…”
Section: Introductionmentioning
confidence: 99%